WHO-Anthro Growth Standard's Effect On Quality and Data On Toddler Nutrition - Agus Hendra Al Rahmad (Universitas Tadulako, 2022)
Indonesia began implementing the WHO-2006 child growth standard in 2010, including Aceh Province. However, it has not used WHO-Anthro to measure the quality of data and information on the nutritional status of children under five. Nutritionists only assess the growth of toddlers using simplified tables and growth charts. The study aims to measure the effect of using WHO-Anthro growth standards on toddlers' quality and nutritional status data.The study used a Quasi Experiment design conducted at the Banda Aceh City Health Office in 2021. The subjects were all nutritionists, namely 22 nutritionists. Data collection was carried out for three months, starting from the pretest and post-test after one month of practice and after two months—the training on using WHO-Anthro application-based growth standards. The data collected was the quality of nutrition data, including timeliness, completeness of information, accuracy, and usefulness. Data were analyzed using the Repeated Measured Anova test at 95% CI. The results found that using WHO-Anthro standards for two months after the intervention had improved the quality of nutrition data to 85.16%. Therefore, there is a statistically significant difference in average data quality between before and after one to two months of using WHO-Anthro (p-value < 0.05). In conclusion, using WHO-Anthro growth standards can improve the quality of data and information on the nutritional status of young children.